Slovak Republic : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that following a sharp downturn in 2009 in the context of the global economic and financial crisis, Slovakia emerged as one of the fastest-growing economies in the European Union, supported in particular by substantial foreign investment in the auto sector and subsequent exports. Growth slowed to 2 percent in 2012 as the impact of exceptionally large investments in 2011 faded. Inflation fell to 1.6 percent in June 2013, and record trade and current account surpluses were recorded in 2012. For 2013, the growth forecast is 0.6 percent, reflecting especially the weakening external environment.